1997
DOI: 10.1002/(sici)1099-1573(199712)11:8<576::aid-ptr174>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular pharmacology of 3-n-butylphthalide in spontaneously hypertensive rats

Abstract: The hypotensive and vasorelaxant effects of 3‐n ‐butylphthalide (BuPh) and its possible mechanisms of action were investigated in spontaneously hypertensive rats (SHR) for the first time. A 13‐day intraperitoneal infusion of BuPh at doses of 2.0 and 4.0 mg/day produced a transient hypotensive effect while a dose of 0.5 mg/day showed a significant hypotensive effect only on day 12. BuPh at 0.5 mg/day had no effect on the plasma and tissue angiotensin converting enzyme (ACE) activities, or on the tissue lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
(21 reference statements)
0
31
0
Order By: Relevance
“…Intraperitoneal administration of BuPh resulted in hypotensive and relaxing effect in the case of contraction induced by phenylephrine and KCl in rat aortic rings, however, no alteration in ACE activity was observed. Blockade of voltageand receptor-operated Ca 2+ channels was suggested to be the probable mechanism (Tsi and Tan, 1997). In another study the hypotensive effect of the plant extract was suggested to be through stimulation of muscarinic receptors (Branković et al , 2010).…”
Section: Apium Graveolens (Celery)mentioning
confidence: 99%
See 1 more Smart Citation
“…Intraperitoneal administration of BuPh resulted in hypotensive and relaxing effect in the case of contraction induced by phenylephrine and KCl in rat aortic rings, however, no alteration in ACE activity was observed. Blockade of voltageand receptor-operated Ca 2+ channels was suggested to be the probable mechanism (Tsi and Tan, 1997). In another study the hypotensive effect of the plant extract was suggested to be through stimulation of muscarinic receptors (Branković et al , 2010).…”
Section: Apium Graveolens (Celery)mentioning
confidence: 99%
“…North America, Europe Blockage of calcium channel, stimulation of muscarinic receptor (Dianat, Veisi, 2015;Chai, Tian, 2010;Supari, 2002;Moghadam, Imenshahidi, 2013;Jorge, Ángel, 2013;Tsi and Tan, 1997;Branković, Kitić, 2010) 4…”
mentioning
confidence: 99%
“…All compounds have been shown to possess hypotensive and vasorelaxant effects. Treatment with 3-n-Butylphthalide at doses of 2.0 and 4.0 mg/day for thirteen days produced a transient hypotensive effect [75]. In another study brazilein is a compound with a non-steroidal skeleton, obtained in a large amount from Caesalpinia sappan ethanol extracts.…”
Section: Found Inmentioning
confidence: 99%
“…Data collection: X-AREA (Stoe & Cie, 2002); cell refinement: X-AREA; data reduction: X-RED32 (Stoe & Cie, 2002); program(s) used to solve structure: SHELXS97 (Sheldrick, 1997); program(s) used to refine structure: SHELXL97 (Sheldrick, 1997); molecular graphics: ORTEP-3 for Windows (Farrugia, 1997); software used to prepare material for publication: WinGX (Farrugia, 1999 (Aoki et al, 1973;Lacova, 1973;Elderfield, 1951;Tsi & Tan, 1997;Bellasio, 1974;Roy & Sarkar, 2005). As part of a continuing study of the interplay between molecular conformation and supramolecular aggregation in 3-substituted phthalides, we now report the structure of the title compound, 3-(3-methoxyphenylamino)isobenzofuran-1(3H)-one, (I) (Fig.…”
Section: Crystal Datamentioning
confidence: 99%